The Pope, Labour, and the Tango: Work, Rest, and Play in the Thought and Action of Benedict XV (1914-22) - Pollard, John Francis (Studies in church history, 2002)
Ever since Leo XIII promulgated his encyclical Rerum novarum, ‘On the Conditions of the Working Classes’, in 1891, successive popes have added to the corpus of Catholic teaching on social/ labour questions. Pius X, for example, published an encyclical specifically addressing the vexed question of ‘interconfessional’ Christian trade unions in Germany, and Pius XI published no fewer than three encyclicals on social questions in the space of twelve months - Quadragesimo anno of May 1931, Nova impendet of October 1931, and Cantate Christi compulsi of May 1932. Recent popes, John XXIII, Paul VI, and John Paul II, have been equally prolific in their commentaries on the labour question.